2013
DOI: 10.5698/1535-7597-13.6.282
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Valproate Exposure and Autism: Long Suspected, Finally Proven

Abstract: CommentaryThe cognitive teratogenic activity of valproate (VPA) is crystallizing with the latest report on the association of in utero VPA exposure and the risk of autism determined from a population-based study utilizing Danish national medical databases. Children born between 1996 and 2006 were followed for the documented occurrence of autism up to 14 years of age, with a mean follow-up of 9 years. The astounding results were that for children born to mothers who took VPA during pregnancy, the risk of childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Other transcriptome studies from our laboratory in human neuronal cells examined whether valproate at clinical dosage can induce changes in the expression of genes associated with neurological disorders including autism [27]. Valproate, an anticonvulsant with similar properties to carbamazepine [28], has been previously found linked to ASD by inducing autism-like phenotypes in mice [29]. Furthermore, studies in humans have found that in utero exposure to valproate is associated with higher risk of ASD [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other transcriptome studies from our laboratory in human neuronal cells examined whether valproate at clinical dosage can induce changes in the expression of genes associated with neurological disorders including autism [27]. Valproate, an anticonvulsant with similar properties to carbamazepine [28], has been previously found linked to ASD by inducing autism-like phenotypes in mice [29]. Furthermore, studies in humans have found that in utero exposure to valproate is associated with higher risk of ASD [29].…”
Section: Discussionmentioning
confidence: 99%
“…Valproate, an anticonvulsant with similar properties to carbamazepine [28], has been previously found linked to ASD by inducing autism-like phenotypes in mice [29]. Furthermore, studies in humans have found that in utero exposure to valproate is associated with higher risk of ASD [29]. Taken together, these studies suggest that exposure to carbamazepine during pregnancy, even at very low concentrations, may pose a liability to the embryo/fetus towards the development of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…When the cohort was restricted to children born to women with epilepsy ( n = 6584), the absolute risk of ASD in the 432 infants exposed to valproate was 4.15% (95%CI, 2.20%–7.81%). In 6125 non‐exposed children, the risk for ASD was 2.44% (95%CI, 1.88%–3.16%) . Thus, there appears to be a definite risk of neurobehavioral issues, including risk of ASD, in those with an in utero exposure to valproate.…”
Section: Prenatal Medication Exposurementioning
confidence: 99%
“…In 6125 non-exposed children, the risk for ASD was 2.44% (95%CI, 1.88%-3.16%). 44 Thus, there appears to be a definite risk of neurobehavioral issues, including risk of ASD, in those with an in utero exposure to valproate.…”
Section: Prenatal Medication Exposurementioning
confidence: 99%
“…Also, as studying autism only in humans is a difficult task that implies a lot of ethical issues, lately there were created some rodent model of this disorder, which are replicating most of its autistic pathophysiological features. In this way, one of the classical models of autism in rodents is based on the observation that valproic acid (VPA), an antiepileptic treatment, when applied to pregnant women results in an increased teratogenic risk of autism [10]. Following the same rationale, the Rodier et al [11] research group induced an animal model of autism, based on the perinatal administration of VPA in an increased dosage (usually 500 or 600 mg/kg), in the 12.5 day of gestation, resulting in a complex range of behavioral and anatomical modifications of autistic-like features in the new-born rats (e.g.…”
mentioning
confidence: 99%